EFFECTIVENESS OF THE SUPER APPLICATION AT THE SUKABUMI CITY COMMUNICATIONS AND INFORMATION OFFICE - Ramadhan, Muhammad Ari; Rachmawati, Ike; FY Basori, Yana Fajar (DIA: Jurnal Administrasi Publik, 2024)
The effectiveness of the Sukabumi Participated Responder (SUPER) application-based complaint service program at the Sukabumi City Communication and Informatics Office is a program created by the Sukabumi City Communication and Informatics Office which aims to facilitate the public in making complaints, criticisms, and suggestions. This research uses Qualitative methods with data collection techniques of observation, interview, and documentation. Data validation using triangulation in this study used source triangulation and technical triangulation. This research uses the theory of measuring effectiveness according to Gibson which has principles namely Production, Efficiency, Satisfaction, Adaptation, and Development. Data analysis uses Creswell's analysis techniques, namely Processing and Preparing, Reading Information, Analyzing, Coding, Describing, and Interpreting. The results of this study indicate that the SUPER program has not been effective because community aspirations still require time in the follow-up process, and the lack of socialization to the community regarding this program has not gone well so there are still many people who do not fully know about the SUPER application. Therefore, it is suggested that the SUPER program needs to improve the implementation of socialization to the people of Sukabumi City and also the Communication and Informatics Office of Sukabumi City needs to improve responsiveness to complaints from the community so that it can create a better program.